STUDI KOMPARATIF BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK NOTEBOOK MEREK ACER DAN ASUS DI PONTIANAK (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TANJUNGPURA) - Purnamasari, Dewi B1021131069 (Jurnal Manajemen Update, 2017)
ABSTRACT This study aims to examine and analyze the comparative study of brand equity on purchase decisions of acer and asus brand notebook products in Pontianak. This research uses a quantitative approach. Population in this research is students from Tanjungpura University Faculty of Business and Economics who have used Asus and Acer notebook. Number of samples each of 50 respondents Asus brand notebook and 50 respondents Asus brand notebook selected by way of purposive sampling, data obtained through questionnaires and then processing data using multiple regression analysis through SPSS20.0 program..The results of this study indicate that the brand equity element Asus Notebook more influence the purchase decision of Asus Notebook in Pontianak. From result of Determination Coefficient test (R2) that Brand Equity of Asus Notebook (73,7%) more influence consumer purchase decision compared to Brand Equity from Notebook Acer (55,1%). While the results of multiple liniear regression test indicate that only Brand Loyalty influencing Purchase Decision to Asus Notebook and Acer Notebook in Pontianak. While the other elements like Brand Awareness, Perceived Quality and Brand Association have no significant positive effect oh the Purchase Decision Asus Notebook and Acer Notebook. Keywords: Brand Equity elements, comparative study and purchase decision.